Analytical Model for Multi-Hazard Resilient Prefabricated Concrete Frame Considering Earthquake and Column Removal Scenarios - Lin, Kaiqi; Lu, Xinzheng; Li, Yi; Zhuo, Weidong; Ye, Lieping (Frontiers in Built Environment, 2018)
Research on multi-hazard prevention and mitigation in building structures is the most recent developing trend in civil engineering. In this study, an analytical model is proposed to calculate the structural resistance of a type of multi-hazard resilient prefabricated concrete (MHRPC) frame under earthquake and column removal scenarios. The MHRPC frame is assembled using prefabricated RC beams and columns, unbonded post-tensioning (PT) tendons, energy-dissipating steel angles, and large rotational shear plates. According to the experimental results, the MHRPC frame exhibits the features of low damage and self-centering under seismic loading. Meanwhile, when subjected to column removal scenarios, the MHRPC frame is proven to demonstrate a high progressive collapse resistance. In order to calculate the seismic and progressive collapse resistance of the MHRPC frame, analytical models for the critical components in the MHRPC frame (PT tendons and steel angles) are compared and selected based on the experimental results and numerical simulations. Furthermore, calculation methods for the seismic and progressive collapse resistance of the MHRPC frame specimens are proposed. The calculation results are validated using the experimental results. This study could provide a reference for the design of MHRPC frame structures, considering both earthquake and progressive collapse.